Utilization of Tebet Eco Park as a Sustainable Tourism Destination - Ryadi, Ragil; Awaloedin, Dipa Teruna; Nugraha, Rizki Nurul (Westscience Press, 2024)
This study aims to analyze the potential utilization of Tebet Eco Park as a sustainable tourism destination. The research was conducted using qualitative methods, using descriptive qualitative analysis and SWOC analysis. The data collection method was carried out by non-participatory field observations, interviews with 10 resource persons, and literature studies. The results showed that ecologically, Tebet Eco Park has a well-maintained biodiversity of flora and fauna. In addition, tourist visits contribute to increasing the turnover of street vendors by up to 30%. Therefore, economic potential can be maximized with several strategies such as management cooperation with cooperatives or community groups. From the cultural aspect, efforts to preserve Betawi culture in the national park are still lacking, so it needs to be improved through festivals and participation of local artists. Meanwhile, various environmentally friendly initiatives have reached 60% of this potential, so they need to be developed by utilizing environmentally friendly technology. In conclusion, Tebet Eco Park is ideal for development as a sustainable tourist destination by integrating economy and culture.